Nicole C. answered • 10/03/12

Increase confidence in math and science, chemistry, algebra II

X^{2} - 2x-13=0 with the following steps:

1. Move the constant term to the right side of the equation.

**x ^{2} - 2x = 13**

2. Multiply each term in the equation by four times the coefficeint of the x^{2} term.

**The coefficient is originally 1, so 4(1) = 4**

** 4(x ^{2} - 2x = 13)**

**4x ^{2 } - 8x = 52**

3. Square the coefficient of the original x term and add it to both sides of the equation.

**The coefficient is originally 2, so (2) ^{2} = 4**

** 4x ^{2} - 8x (+4)= 52 (+4) **

** 4x ^{2} - 8x + 4 = 56**

4. Take the square root of both sides.

** √(4x ^{2} - 8x + 4) = √(56)**

** √4(x - 1)(x - 1) = √(4)(14)**

** 2(x - 1) ^{ } = 2√14**

5. Set the left side of the equation equal to the positve square root of the number on the right side and solve for x.

** 2(x - 1) = 2√14 change 2√14 into a decimal**

** 2(x - 1) = 7.48 divide both sides by 2**

** (x - 1) = 3.74 add 1 to both sides **

** x = 4.74**

6. Set the left side of the equation equal to the negative square root of the number on the right side and solve for x.

**2(x - 1) = - 7.48 **

**(x - 1) = - 3.74 **

**x = -2.74**

7. Set the left side of the equation equal to the negative square root of the number on the right side of the equation and solve for x.

**I think this is a repeat of #6**

Nicole C.

Thanks for the feedback.

10/04/12

Pam K.

Great, thank you so much. I was stuck at step 3. I have several others to do, so this will help.

10/04/12